( 1 + α 2 ) ( 1 + β 2 ) ( 1 + γ 2 )
If α , β and γ are the roots of x 3 + x + 1 = 0 , then find the value of the above expression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By Vieta's formula.
α
+
β
+
γ
=
0
α
β
+
α
γ
+
β
γ
=
1
α
β
γ
=
−
1
⟹ ( 1 + α 2 ) ( 1 + β 2 ) ( 1 + γ 2 )
1 + ( α 2 + β 2 + γ 2 ) + ( ( α β ) 2 + ( β γ ) 2 + ( γ α ) 2 ) + ( α β γ ) 2 )
1 + ( − 2 ) + 1 + 1 = 1
Re-write as α β γ ( α + α 3 ) ( β + β 3 ) ( γ + γ 3 ) = − 1 ( − 1 ) ( − 1 ) ( − 1 ) as Vieta's theorem gives the product of the roots equals -1. Answer is 1.
Notice that x 3 + x + 1 is a function.
Let f ( x ) = x 3 + x + 1 . Also notice that, 1 + α 2 ) ( 1 + β 2 ) ( 1 + γ 2 ) = f ( i ) ⋅ f ( − i ) , where ′ i ′ is imaginary unit. f ( i ) ⋅ f ( − i ) = 1 .
Problem Loading...
Note Loading...
Set Loading...
The equation x 3 + x + 1 can be written as ( x − α ) ( x − β ) ( x − γ ) .
According to Vietta we can create these 3 equations
Now, if we combine the 1st and 2nd equations we can see that α ( β + γ ) + β γ = β γ − α 2 = 1 . This goes for all 3 roots. This means that β γ = 1 + α 2 .
Now if we look at our question ( 1 + α 2 ) ( 1 + β 2 ) ( 1 + γ 2 ) We can swap 1 + α 2 with β γ and 1 + β 2 with α γ and 1 + γ 2 with α β .
This will give us the result of ( α β ) ( α γ ) ( β γ ) = α 2 β 2 γ 2 = ( α β γ ) 2 = 1